The Urgency of Environmental Education in Kurikulum Merdeka: A Geophilosophical Approach - Rangga Kala Mahaswa; Gloria Bayu Nusa Prayuda; Luthfi Baihaqi Riziq (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Environmental Education (EE) is currently receiving broad attention in formulating and implementing fostering students' character to be more environmentally conscious. This issue is also entangled with the global commitment to create a sustainable society. Indonesia experienced a curriculum transition from the K13 to Merdeka curricula; thus, integrating environmental problems into the new curricula is important. In general, the implementation of EE in schools can be divided into two approaches: integrating it into a specific syllabus and incorporating it into extracurricular or ceremonial school activities. Several obstacles have been identified during the implementation of EE, especially at the high school level and its equivalents, including EE being perceived as a burden on students' study time, a lack of coordination among relevant institutions, insufficient funding, and ineffective EE program formats. These findings are based on focus group discussions (FGDs) conducted in-depth interviews with Adiwiyata High School students to determine the implementation of PLH in schools and supporting literature reviews. To address these obstacles, this research adopts a geophilosophical perspective as a novel approach to support education and curricula that promote sustainable environmental awareness, both in affective and practical-contextual actions, by considering the importance of geographical agency in teaching and learning. Consequently, it was discovered that the geophilosophical approach could serve as an alternative model for curriculum development that is more flexible to strengthen Kurikulum Merdeka.